Coupled 3D master equation and 1D drift‐diffusion approach for advanced OLED modeling. Issue 5 (21st April 2020) - Zeder, Simon; Kirsch, Christoph; Aeberhard, Urs; Blülle, Balthasar; Jenatsch, Sandra; Ruhstaller, Beat
Abstract: A novel simulation approach for excitonic organic light‐emitting diodes (OLEDs) is established by combining a continuous one‐dimensional (1D) drift‐diffusion (DD) model for the charge carrier dynamics with a three‐dimensional (3D) master equation (ME) model describing the exciton dynamics in a multilayer OLED stack with an additional coupling to a thin‐film optics solver. This approach effectively combines the computational efficiency of the 1D DD solver with the physical accuracy of a discrete 3D ME model, where excitonic long‐range interactions for energy transfer can be taken into account. The coupling is established through different possible charge recombination types as well as the carrier densities themselves. We show that such a hybrid approach can efficiently and accurately describe steady‐state and transient behavior of optoelectronic devices reported in literature. Such a tool will facilitate the optimization and characterization of multilayer OLEDs and other organic semiconductor devices. Abstract : An advanced modeling approach using a hybrid drift‐diffusion and master equation model is established. It is shown that this approach can efficiently and physically accurately describe optoelectronic devices as reported in literature.